Is Tik-Tok a Helpful Application for Improving College Students’ English Pronunciation? - Merizawati, Henny; Luana, Luana; Pakpahan, Marnangkok; Ariesta, Naura; Elliot, McCarty (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Currently English is an international language that makes it easy to use it to be able to communicate between each other. This study aims to provide an overview of the use of social media as a medium of learning English to improve pronunciation or pronunciation, using the TikTok application as a learning medium. This research uses descriptive qualitative methods on 10 6th semester students majoring in English at Mahmud Yunus Islamic State University Batusangkaryang who have used the TikTok application. In collecting data, researchers used in-depth interviews with participants to explore information about TikTok as a learning media in improving pronunciation. From the interview, the researcher analyzed each answer from the respondent and the researcher found that the use of TikTok as a learning medium could improve the respondent's pronunciation or fluency in speaking English. Based on the results that researchers get, most students state that the TikTok application can improve their pronunciation skills and TikTok can be used as a learning media for pronunciation in English because it has many benefits and is effective in helping students and lecturers in teaching and learning activities.